REGULATION AND LEGAL IMPLICATIONS OF CRYPTOVALUTA: A LITERATURE REVIEW OF GLOBAL POLICIES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This research explores the regulations and legal implications relating to cryptovaluta through a literature review of global policies. Countries have taken diverse approaches to regulating cryptovaluta, the main objectives of which are to provide legal certainty, protect consumers, and prevent illegal activities such as money laundering and terrorism financing. Market stability and security are key aspects of these regulations, with consumer protection and market transparency prioritised. However, challenges in policy alignment between countries are significant due to the need to prevent regulatory arbitrage and address cross-border criminal offences. This research highlights the importance of international collaboration and the development of common standards to create a consistent and adaptive regulatory framework, capable of supporting the wider and safer adoption of cryptovaluta, providing substantial global economic benefits in the future.